The protocol for the Be Our Ally Beat Smoking (BOABS) study, a randomised controlled trial of an intensive smoking cessation intervention in a remote Aboriginal Australian health care setting. - Marley, J.; Atkinson, D.; Nelson, C.; Kitaura, T.; Gray, Dennis; Metcalf, S.; Murray, R.; Maguire, G. (BioMed Central Ltd, 2012)
Background: Australian Aboriginal peoples and Torres Strait Islanders (Indigenous Australians) smoke at much higher rates than non-Indigenous people and smoking is an important contributor to increased disease, hospital admissions and deaths in Indigenous Australian populations. Smoking cessation programs in Australia have not had the same impact on Indigenous smokers as on non-Indigenous smokers. This paper describes the protocol for a study that aims to test the efficacy of a locally-tailored, intensive, multidimensional smoking cessation program. Methods/Design: This study is a parallel, randomised, controlled trial. Participants are Aboriginal and Torres Strait Islander smokers aged 16 years and over, who are randomly allocated to a ‘control’ or ‘intervention’ group in a 2:1 ratio. Those assigned to the ‘intervention’ group receive smoking cessation counselling at face-to-face visits, weekly for the first four weeks, monthly to six months and two monthly to 12 months. They are also encouraged to attend a monthly smoking cessation support group. The ‘control’ group receive ‘usual care’ (i.e. they do not receive the smoking cessation program). Aboriginal researchers deliver the intervention, the goal of which is to help Aboriginal peoples and Torres Strait Islanders quit smoking. Data collection occurs at baseline (when they enrol) and at six and 12 months after enrolling. The primary outcome is self-reported smoking cessation with urinary cotinine confirmation at 12 months.Discussion: Stopping smoking has been described as the single most important individual change Aboriginal and Torres Strait Islander smokers could make to improve their health. Smoking cessation programs are a major priority in Aboriginal and Torres Strait Islander health and evidence for effective approaches is essential for policy development and resourcing. A range of strategies have been used to encourage Aboriginal peoples and Torres Strait Islanders to quit smoking however there have been few good quality studies that show what approaches work best. More evidence of strategies that could work more widely in Indigenous primary health care settings is needed if effective policy is to be developed and implemented. Our project will make an important contribution in this area.